The Role of Media in Creating Values of Nationalism in Pakistan - Munawar Sabir (Journal of Political Studies, 2011)
The nationalism is basically a concept referring to the areas of culture, history, language, and politics. The paper is emphasizing the concept of role played by media in creating the values in nationalism. The first section of the report is describing the concept of nationalism in general and in Pakistan’s perspective. The second section of the paper is discussing the diversification of nationalism within Pakistan. The discussion is followed by the third section which is illustrating the issues of nationalism which includes ethnic issues as the base of conflicts for realizing the nationalism. The fourth section is discussing the general concept and over view including issues and different phases faced by media of Pakistan and the role it plays in nationalism. The last section is a concluding part discussing the new era globalization and role of media in nationalism. In this section, it is concluded that the media has transformed in the past few years so rapidly that it creates a remarkable and sound picture of nationalism for Pakistan apart from the fact that it is still facing lots of issues and troubles.